+0  
 
0
46
1
avatar+389 

What are the solutions to the equation f(x)=g(x)f(x)=g(x)?

Hev123  May 29, 2018

Best Answer 

 #1
avatar+74 
+1

\(x^2 - 4x + 3 = -x^2 +3 \)

 

\(2x^2 - 4x\)

 

\(2x(x-2)\)

 

\(x = 0, 2\)

Confusedperson  May 29, 2018
 #1
avatar+74 
+1
Best Answer

\(x^2 - 4x + 3 = -x^2 +3 \)

 

\(2x^2 - 4x\)

 

\(2x(x-2)\)

 

\(x = 0, 2\)

Confusedperson  May 29, 2018

10 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.